Identifikasi Flu Burung H5N1 pada Unggas di Sekitar Kasus Flu Burung pada Manusia Tahun 2011 di Bekasi (AVIAN INFLUENZA H5N1 IDENTIFICATION IN AVIAN SPECIES SURROUNDING AVIAN INFLUENZA H5N1 HUMAN CASES IN BEKASI, WEST JAVA, 2011) - Hewajuli, Dyah Ayu; Dharmayanti, Ni Luh Putu Indi (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
H5N1 subtype Avian Influenza (AI) virus is the causal agent  of AI disease in humans. In Indonesia,the first human AI occurred in Tangerang 2005.  Human AI in Indonesia has now spread into 12 provinces,including West Java, Jakarta, Banten, North Sumatra, East Java, Central Java, Lampung, South Sulawesi,West Sumatra, South Sumatra, Riau, and Bali. Until 2011, the total human AI cases were 182 cases  with150 deaths. This study was conducted to identify of H5N1 AI virus in birds in area surrounding a humanAI human case  in Bekasi city  in March 2011 and to investigate its role in the spread of AI to humans usingmethods of Hemaglutination Inhibition (HI ), and Reverse Transcriptase-Polymerase Chain Reaction(RT-PCR). The result showed that 80% of birds in the area surrounding AI  surrounding H5N1 AI humancase in Bekasi 2011 were antibody negative  against  H5N1-AI virus. Antibody against H5N1-AI viruswith the titer less than 4 log 2 was detected in 4.4%  of birds and  with antibody titer 04 4-7 log 2 in 15%of birds. By RT-PCR, H5N1 AI virus was not detected in 47.6% of bird samples. H5 positive and N1negative  AI virus was detected in  30.2% samples.  Only 11.2% samples showed positive for H5N1 AI virus.The results suggest that H5N1-AI virus affecting birds may have a positive role in transmitting to thevirus to human in Bekasi 2011.
Keywords: H5N1subtype AI virus, birds, HI and RT-PCR